Epidemiology of Sexually Transmitted Diseases Among Pregnant Adolescents. Issue 5 (1994) - Gittens, Lisa N.; Nichols, Rhonda R.; Apuzzio, Joseph J.
Abstract : Objective: The purpose of this study was to determine the epidemiology of sexually transmitted diseases (STDs) among pregnant adolescents. Methods: Charts of all patients (n = 735) who attended the Maternal and Infant Care Clinic at University Hospital, Newark, NJ, between July 1, 1991, and June 30, 1992, were reviewed for STDs which included gonorrhea, chlamydia, syphilis, and human immunodeficiency virus (HIV). At the first prenatal visit, each registrant had endocervical specimens obtained to detect gonorrhea and chlamydia. A serum sample was obtained for syphilis screening. HIV testing was made available to all patients and testing was done on a voluntary basis. The same STD screening that was done at the initial visit was repeated at 28 and 36 weeks. Results: Twenty-five percent of patients tested positive for one or more STDs. The mean patient age was 17.3 years. The mean gestational age at first visit was 19.5 weeks. The mean number of visits was 7.3. The following STDs were identified: 4.8% of patients tested positive for gonorrhea, 20.9% tested positive for chlamydia, and 1.7% tested positive for syphilis. Twenty-one percent of patients had a positive STD diagnosed at the initial visit. Another 4.8% of patients had an STD diagnosed at some time after the initial visit when the initial screen was negative for STDs. An additional 1% of patients who initially tested positive for an STD had subsequent screening which revealed another STD (different organism). Seven patients tested HIV positive. Sixty-one percent of patients with STDs agreed to HIV testing. One patient had HIV coexistent with another STD. Conclusions: Pregnant adolescents are at risk for multiple STDs. HIV testing should be offered. STD screening should be repeated in the third trimester in adolescent patients.